BEST PRACTICES FOR STRENGTHENING STUDENTS’ PANCASILA PROFILE WITH THE THEME OF ENTREPRENEURSHIP - Roslani Supinah; Ishaq Nuriadin; Cucu Suryani (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2023)
This study aims to obtain detail information about best practices for strengthening students' Pancasila profiles with the theme of entrepreneurship with the sub-theme of building a creative and innovative culinary entrepreneurial spirit in youth. Through this project, students are expected to be able to develop and achieve specifically the three dimensions of the students' Pancasila profile, namely independence, creativity and cooperation. The type of research used is qualitative research with a case study strategy. The research was conducted at SMA Negeri 6 Kota Tangerang Selatan from September to December 2022. Research data was obtained through observation, documentation and interviews. The research subjects were teachers as project facilitators and coordinators, as well as class X students for the 2022/2023 academic year. The project activity on the theme of entrepreneurship is carried out in five stages of the planning flow. From the results of the study, it was concluded that the project activities on the theme of entrepreneurship which were carried out at SMA Negeri 6 Kota Tangerang Selatan went well. Students get some benefits from project activities and can achieve goals in accordance with the character of the students' Pancasila profile, namely independent, creative and cooperative. There were several obstacles encountered related to the facilitators and students during the entrepreneurship themed project activities.